Realizing identity and overcoming barriers: Factors influencing female Japanese Paralympians to become coaches - Itoh, M.; Hums, M. A.; Arai, A.; Ogasawara, E. (International Journal of Sport & Health Science, 2018)
The purpose of this qualitative study was to (a) determine structural barriers that must be overcome to cultivate female leaders and coaches and (b) study the development of a support system for female leaders and coaches. This study relied on in-depth interviews as the primary means of collecting data. Formal semi-structured interviews were conducted with seven former or currently active female Paralympians, including some who were current coaches. After analyzing the participants' responses, five distinct themes emerged: (a) social identity, (b) challenges of "double minority status" as women and persons with a disability, (c) underrepresentation of women as Paralympic coaches, (d) athletes wanting to be coaches indicating they needed formal training, and (e) current coaches feeling overwhelmed by task requirements not related directly to working with athletes. The first of these relate to realizing identity and the other four to overcoming barriers. The results offer insight into the career challenges and career perceptions of coaches and also former or currently active female Paralympians. The results provide researchers with insight into the status of careers of women in a segment of the sport industry, the Paralympic Movement, which has not yet been thoroughly explored.